Analysis of Appropriate Marketing Strategies for Catfish Farming in Duren Mekar Subdistrict as a Contribution to Achieving SDGs for Poverty Alleviation and Increasing Welfare - Aprillia Eka Lestari; Harlis Setiyowati (Manajemen dan Kewirausahaan, 2023)
One of the important sources of income in Duren Mekar District, Depok, West Java is catfish cultivation. The harvest is a benefit for the local community. This research aims to analyze the strengths, threats, opportunities, and challenges of catfish cultivation to improve welfare in supporting the achievement of the Sustainable Development Goals (SDGs). Qualitative methods are used with analytical techniques Strengths, Weaknesses, Opportunities, Threats (SWOT), and Analytical Hierarchy Process (AHP) method. The results of the SDG's contribution are SDGs 1 in reducing poverty and SDGs 8 in developing jobs and economic growth. The SWOT results show that its strengths are the ease of cultivating catfish and supporting regional conditions. The opportunities are a high market, low competition, and government policy support that supports economic sustainability. The threat of catfish farming regarding feed prices which tend to be high is the focus so that operational activities can run smoothly. Weaknesses regarding knowledge about online marketing. Meanwhile, the AHP results show that alternative marketing strategies that can be prioritized by catfish farming business actors, both government and private, are maintaining and maintaining the quality of catfish and carrying out maintenance on water ponds with a weight of 0.197 and building large areas of land. Network in marketing catfish with local government or residents with a weight of 0.159. Therefore, there is a need for access to capital from the relevant agencies for operational costs such as catfish feed.